A novel technique of managing severe lower airway obstruction during emergent interventional bronchoscopy. Issue 2 (August 2017) - Mehta, Arpan; Mordecai, Luke
Abstract : Abstract : Transnasal Humidified Rapid Ventilatory Exchange (THRIVE) is being progressively used for providing oxygenation and gas exchange for a variety of short procedures requiring general anesthesia.1 This technique may be ideally suited for flexible bronchoscopy performed under the target controlled intravenous (IV) infusions (TCI) of propofol and remifentanil. Such anesthesia regimen afford superior oxygenation, simplifies airway management, improves operating conditions, and promotes haemodynamic stability and rapid patient emergence from anesthesia. This case report describes the use of the THRIVE‐TCI technique for emergency bronchoscopy in a patient with acute respiratory distress caused by extensive bronchial obstruction. Interventional bronchoscopy, bronchial biopsy, debulking and stent insertion were successfully performed, and the patient was later weaned off THRIVE in the Intensive Care Unit.